Penyakit Mental Dalam Perspektif Tasawuf - Ervina Zahrah Yasminiah; Hana Fadia Rihadatul’aisyi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Sufism is a branch of Islam that emphasizes spiritual pursuit and self-purification to achieve closeness to God. In the Sufism perspective, mental illness is not only seen as a medical condition but also as a spiritual crisis. Mental illness is often thought to be the result of an imbalance in a person's relationship with God and their environment. Sufis believe that true mental health can only be achieved through cleansing the heart and soul of negative traits such as envy, hatred and greed. This process involves dhikr (remembrance of God), meditation and other spiritual practices aimed at strengthening the relationship with God and improving morals. Sufism also emphasizes the importance of living a simple and loving life and avoiding materialistic temptations that can lead a person away from the spiritual path. Thus the treatment of mental illness in Sufism does not only focus on the psychological aspect but also includes the spiritual dimension, which is considered essential for achieving balance and inner peace. This view emphasizes that true healing requires a holistic approach that integrates psychological therapy with spiritual practices, so that a person can again find the meaning of life and closeness to God, which ultimately brings peace and mental well-being.